Panchromatic sensitization of new terpyridine ligated thiocyanate-free Ru-complex. (August 2019) - Swetha, T.; Rana, Prem Jyoti Singh; Islam, Ashraful; Singh, Surya Prakash
Graphical abstract: Two new Ru-based complexes GS1 and GS2 are synthesized. The DSSCs device with pyrene substituted sensitizer have shown panchromatic sensitization. Highlights: Synthesized a novel Ru based complexes for DSSCs Application. The device with these complexes showed efficient panchromatic sensitization over the entire visible wavelength range extending into the near-IR region. The power conversion efficiency of 3.25% achieved. Abstract: Two new thiocyanato-free Ru sensitizers GS1 and GS2 having substitutions at the central pyridyl group of the terpyridine ligand successfully synthesized. GS1 and GS2 were used as photosensitizers for DSSCs devices. These sensitizers were characterized by 1 H NMR, FT-IR, UV–visible, and differential pulse voltammetry studies. The optical and electrochemical properties of these sensitizers were compared with N749 dye. The fabricated device with these complexes portrays an efficient panchromatic sensitization which covers the entire region from visible to NIR. Time-correlated single photon counting (TCSPC) experiment was also performed to study the charge carrier dynamics of both the sensitizers. The average excited state-life time of the GS1 and GS2 sensitizers on TiO2 is 4.04 ns and 3.07 ns respectively, which was much better compared to the reference sensitizer (0.25 ns). Among these two sensitizers, GS2 exhibited a maximum overall power conversion efficiency of 3.25% under standard air mass 1.5 irradiation (100 mW cm −2 ) with the Jsc = 10.073 mA/cm 2, the Voc = 0.451 V, and the FF = 0.714.